Perbandingan Metode Median Filtering dengan CLAHE dalam Mengidentifikasi Koloni Bakteri - Nilasari, Ni Ketut Novia; Divayana, Yoga; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2022)
Abstract — The exact estimation of the number of colonies or Colony Forming Units (CFUs) is frequently used in microbiology research, particularly in the field of bacteria. The number of colonies that develop per gram or milliliter of sample is estimated by multiplying the number of plates, the dilution factor, and the volume used [1]. Counting the number of bacterial colonies can be used to determine a bacterium's growth rate. The cup count method is commonly used to accomplish this manually. An instrument called a colony counter can help with colony counting utilizing the cup count method. This technology works by using a pen connected  to a counter to mark the colonies that have been counted. However, because the colony size is tiny and the number of colonies counted is huge, this can lead to inaccuracies, and the same difficulties can happen with manual colony computations. Digital image processing technology has been extensively developed for use in a variety of fields. Researchers had previously undertaken a similar study that attempted to count bacterial colonies and had a 94 percent accuracy rate, but some colonies were not spotted because they were filtered during preprocessing , so they looked into it further. Keywords —Bacteria Colony, Image Processing, Preprocessing ,